THE DESIGN OF WORK FACILITIES BASED ON WORKERS POSTURE ANALYSIS IN TOFU PRODUCTION MSME - Andjar Sari, Sanny; ST Salammia LA; Suardika, Ida Bagus (Journal of Sustainable Technology and Applied Science (JSTAS), 2021)
Work facilities following the user's needs are critical because they support the production process for increased productivity. Currently, the tofu production process at Mr Samingin's MSMEs uses manual equipment to feel pain in their body parts when doing work every day. Making tofu begins with washing the soybeans thoroughly, then soaking the soybeans in water for 2 to 3 hours. Sometimes, it needs 7 hours, depending on the type of soybeans. In this soaking process, the soybeans will expand and then cleaned again by washing them several times. The next step is to grind the soybeans into powder with a grinding machine then boiled them. Then, filter the soybean porridge with a cloth to separate the pulp to be processed and the rest of the cooking water. This stage is very tiring as it is done manually by filtering in a shake. In addition, in the process of pressing tofu, there is a lack of attention to workers' work posture, which will impact work-related pain, especially if it is done monotonously and repeatedly. This study used the Rapid Upper Limb Assessment (RULA) analysis method as a guide in designing tofu screening work facilities. It is expected that improvements to work facilities can increase worker productivity at tofu production MSME.